The African Union: Reading the Signs of Hope in Our Continent (Hekima Review, 2024)
The last eleven months of this year have given us a mixed bag of hope and despair in Africa. One conference followed the other, in or about Africa and its plight in the fast-changing world. Whatever causes are put forward for the ragbag of Africa's hope as well as despair, one conclusion is that the reason we hold so tightly to hope is because we face so many challenges in our continent.